2019
DOI: 10.29309/tpmj/2019.26.08.3749
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of visual outcomes in patients undergoing small incision cataract surgery versus phacoemulsification at Divisional Headquarters Hospital, New Mirpur, Azad Kashmir.

Abstract: Cataract extraction is one of the commonest surgical procedures in Ophthalmology globally. Extracapsular cataract extraction ECCE), through a small incision (SICS), with insertion of an intraocular lens has been the most widely used method from 1990s until recently. Technological advances have led to the increasing use of phacoemulsification (PE) to emulsify and remove the lens. The technique requires a smaller incision, but requires substantial capital investment in theatre equipment. In this we compared the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…Then, the intervention that uses more in this study was Small Incision Cataract Surgery compared to Phacoemulsification. This result was same to Hamid and Habibullah's study who found more patients used Small Incision Cataract Surgery compare to Phacoemulsification [6]. In Bhandari and Bhandari's study found that the number of patients with Small Incision Cataract Surgery and Phacoemulsification was the same [7].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Then, the intervention that uses more in this study was Small Incision Cataract Surgery compared to Phacoemulsification. This result was same to Hamid and Habibullah's study who found more patients used Small Incision Cataract Surgery compare to Phacoemulsification [6]. In Bhandari and Bhandari's study found that the number of patients with Small Incision Cataract Surgery and Phacoemulsification was the same [7].…”
Section: Discussionsupporting
confidence: 77%
“…They showed no difference between UCVA 6/12-6/60 post Small Incision Cataract Surgery and post Phacoemulsification. This result was influenced by the frequent risk factors found in both groups, namely the emergence of other eye diseases after surgery such as postoperative complications, but Hamid and Habibullah explained that SICS produced better results due to costeffectiveness problems [6].…”
Section: Discussionmentioning
confidence: 99%